Role of Dynamic Perfusion CT in Pancreatic Adenocarcinoma - Yadav, Ajay K.; Yadav, Neha; Yadav, Rohit P.; Taparia, Sushil; Dev, Binit; Pandit, Narendra (Indian Journal of Radiology and Imaging, 2025)
The aim of this study is to evaluate the utility of perfusion CT (PCT) in the diagnosis of pancreatic ductal adenocarcinoma (PDAC).In this ethically approved prospective study, PCT was performed in 71 patients with histologically proven PDAC. Perfusion parameters studied included blood flow (BF), blood volume (BV), permeability surface area product (PS), time to peak (TTP), peak enhancement intensity (PEI), and mean transit time (MTT). Forty-four controls with no pancreatic pathology were also studied.Out of 71 patients, 43 (60.56%) were males and 28 (39.44%) were females, with male:female ratio of 1.54, and the mean age of the patients was 50.62 ± 13.86 years. The mean size of the masses was 4.47 ± 2.43 cm (range: 1.3–12 cm). Among the perfusion parameters, BF and BV were found to be the most reliable for the diagnosis of pancreatic adenocarcinoma. They were reduced in PDAC (BF: 19.54 ± 19.85 mL/100 mL/min and BV: 5.14 ± 3.82 mL/100 mL) as compared with normal controls (BF: 96.91 ± 39.09 mL/100 mL/min and BV: 30.45 ± 12.90 mL/100 mL) and the difference was statistically significant (p = 0.0001). Based on ROC analysis, cut-off values of 55.25 mL/100 mL/min for BF and 14.42 mL/100 mL for BV yielded optimal sensitivity (97.2% for BF and 98.6% for BV) and specificity (91% for BF and 91% for BV) for the diagnosis of pancreatic adenocarcinoma.PCT parameters are useful in making an imaging diagnosis of PDAC and useful tool to detect isodense pancreatic masses. Approximated values of BF and BV perfusion parameters may serve as independent diagnostic predictors for the diagnosis of PDAC.
Keywords: pancreas; perfusion; computed tomography; adenocarcinoma